TRANSFORMATION OF AUDIT SERVICE - Guzal Yashinovna Babaeva; Sagdiana Doniyor qizi Namozova (KONFERENSIYALAR, 2025)
In this paper, the authors attempt to formulate a new definitionof the concept of modern audit as a process in which internal auditors useinformation and communication technologies (ICT) in conjunction withanalytical procedures to collect electronic evidence, interact with the auditee,and prepare a report on the reliability of financial data and internal controlsystems regardless of the auditor's physical location. Based on research onvirtual teams and analysis of internal audit activities, we present a researchframework that defines the areas in which ICT and automated audit analyticsallow auditors to work remotely, reduce travel expenses and wait times, andimprove efficiency and coverage.